E-Cigarette-Only and Dual Use among Adolescents: Emerging Behaviours with Different Risk Profiles. (20th October 2021) - Bowe, A; Doyle, F; Stanistreet, D; Durcan, M; Major, E; O'Connell, E; Kavanagh, P; O'Donovan, D
Abstract: Background: E-cigarette-only use and dual-use are emerging behaviours among adolescent nicotine product users which have not yet been sufficiently explored. This study examines the epidemiology of, and the factors associated with, nicotine product use in adolescence, specifically defined as e-cigarette only, conventional cigarette only and dual-use. Methods: This is a cross-sectional analysis of the 2018 Planet Youth survey completed by 15-16 year olds in the West of Ireland. Current nicotine product use, defined by use at least once in the past 30 days, was categorised as e-cigarette only, conventional cigarette only, and dual-use. The characteristics and risk factor profiles of the population are described, according to nicotine product use, using chi-square tests for categorical data and t-tests for continuous data. A main effects multinomial logistic regression model was used to compare the association between potential risk and protective factors across categories of use. Results: Among 4422 adolescents 22.1% were current nicotine product users, consisting of 5.1% e-cigarette only users, 7.7% conventional cigarette only users, and 9.3% dual-users. Risk factor profiles differed across categories of use. Frequent participation in team sport significantly reduced the odds of conventional cigarette and dual use but had no association with e-cigarette only use (Cig only: adjusted odds ratio (AOR) 0.63, 95% confidence interval (CI) 0.44-0.90; Dual-use: AOR 0.63, 95% CI 0.43-0.93, E-Cig only: AOR 1.31, 95% CI 0.87-1.97, p = 0.199). Similarly, having higher value for conventional social norms reduced the odds of conventional cigarette and dual use but not e-cigarette only use. Conclusions: This is the first study to show, among a generalisable sample, that dual-use is the most prevalent behaviour among adolescent nicotine product users in Ireland. Risk factor profiles differed significantly across categories of use with important implications for youth tobacco control policy. Key messages: This is the first study to show that dual use of conventional and electronic cigarettes, an under-researched behaviour, is the most prevalent form of nicotine product use among adolescents in Ireland. Risk factor profiles of e-cigarette only, conventional cigarette only, and dual users differ significantly, and this has important implications for prevention initiatives and tobacco control policy.